Characterization of Chronic Mechanical Irritation in Oral Cancer - Jerónimo P. Lazos; Eduardo D. Piemonte; Hector Eduardo Lanfranchi; Mabel N. Brunotto (International Journal of Dentistry)
Objective. Oral mucosa could host many lesions originated by chronic mechanical irritation (CMI) from teeth or dentures, and it has been proposed as risk factor for oral cancer. Nevertheless, the features of CMI factors in oral cancer and other lesions are not assessed. The aim of this study is to describe CMI features regarding type (dental, prosthetic, and/or functional), localization, and time span. Materials and Methods. Three groups were studied in this cross-sectional study: Oral Cancer (OC); Chronic Traumatic Ulcer (CTU); and Benign Irritative Mechanical Lesions (BIML). All sources of mechanical irritation were included: dental, prosthetic, and functional. Results. 285 patients (176 females, 109 males) were studied: OC = 38, CTU = 44, and BIML = 203. The most frequent CMI factor was dental, followed by functional and prosthetic in all groups; 76.5% (n=218) presented functional factors. Buccal mucosa (45%) and tongue (42%) were the most affected sites. Time of action of CMI displayed statistically significant differences between BIML, CTU, and OC groups, with a mean of 21, 33, and 49 months, respectively. Conclusions. CMI should be properly recorded with as much detail as alcohol and tobacco consumption. CMI associated lesions are produced by dental or prosthetic factors, usually in relation to functional factors, involving mainly tongue and buccal mucosa.